Use of E-Comic media through canva to increase the Maharah Kitabah - Khalis, Salsabila; Sopian, Asep (Aksara: Jurnal Bahasa dan Sastra, 2023)
Every language skill must have its disadvantages and advantages, as well as writing skills (Maharah Kitabah). Based on the results of observations, there are difficulties in writing skills, namely different backgrounds When attending elementary school, lack of practice and uninteresting material taught by educators to students from the description above shows that there is a need for interesting media to increase enthusiasm for learning in students in writing. One media that can increase students' enthusiasm in writing skills is e-comic. E-comic is a digital comic that is used to convey information about the field of knowledge excitingly and entertainingly, besides the use of e-comics are more practical and can be opened anywhere and anytime as long as they have a file or access link; e-comic is also an attraction for students so that it can help in learning Arabic, especially in maharah kitabah. The research was conducted at SMP Daarut Tauhiid Bandung in class VII, which aimed to determine whether e-comic media was influential in improving maharah kitabah. This study used a quantitative approach with a quasi-experimental design in the form of a Non-Equivalent Control Group Design, which was divided into two research groups: a control group and an experimental group. Data is taken using tests in the form of pretest and post-test. The results showed that e-comic media using Canva was influential in increasing Maharah kitabah with an increase of 23.5; besides that, it was strengthened by a signification value of 0.00, meaning there is a difference in student learning outcomes. This research is expected to be able to use e-comic as one of the supporting media for learning Arabic, especially in Maharah KitabahKeywords: E-comic, Canva, Maharah kitabah